Mutu Produk, Nilai dan Kepuasan Pelanggan dalam Pandangan Islam - Endraswati, Hikmah (Asy-Syir'ah: Jurnal Ilmu Syari'ah dan Hukum, 2011)
If producers want to attract new costumers or to defend the old one, they must produces product which can satisfy the customers need and want, products which offer value added to customers and product which have high quality but low prices. Through innovation of the product, companies can compete with the ohters. If the companies can do better than the others, companies will get high return in the future like high profit, customer satisfaction, customer loyalty and higher market share. In this paper, we explain about quality of the product, value and customer satisfaction in islamic perspectives.